Exploring the Economic Potential of The Region: Spatial Analysis of Key Sectors for Food Security in Lampung - Resha Moniyana Putri; Andrian, Thomas; Purwaningsih, Vitriyani Tri; Irham, Ahmad Rowatul; Fauzi, Arya Radinsyah; Rozak, M. Ikhsan Nur; Lissa, Nur (Efficient: Indonesian Journal of Development Economics, 2025)
Food security is a strategic issue and a priority for national development in Indonesia, particularly in provinces with significant agricultural potential such as Lampung. This study aims to identify leading and potential sectors that contribute to strengthening food security by applying Location Quotient (LQ), Growth Ratio Model (GRM), Overlay Analysis, and Spatial Analysis. The LQ results indicate seven basic sectors, including food crops, agricultural services, livestock, fisheries, plantations, horticulture, and the food and beverage industry. Further analysis through GRM and Overlay shows that livestock and the food and beverage industry are categorized as leading sectors, while food crops, agricultural services, fisheries, plantations, and horticulture are identified as potential sectors. Spatial analysis highlights Central Lampung, East Lampung, South Lampung, Tulang Bawang, and North Lampung as key regions with sectoral specialization, supported by natural resources, infrastructure, and industrial networks. The findings demonstrate that Lampung Province plays a vital role as a national food barn, but challenges remain, including land conversion, productivity disparities, and post-harvest management. Therefore, integrated policies that combine sectoral revitalization, spatial planning, and sustainable management are required. This research provides a comprehensive foundation for formulating regional economic development strategies to enhance food security resilience in Lampung Province.